A comprehensive profile of genomic variations in the SARS-CoV-2 isolates from the state of Telangana, India. (15th March 2021) - Gupta, Asmita; Sabarinathan, Radhakrishnan; Bala, Pratyusha; Donipadi, Vinay; Vashisht, Divya; Katika, Madhumohan Rao; Kandakatla, Manohar; Mitra, Debashis; Dalal, Ashwin; Bashyam, Murali Dharan
Abstract : The novel severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) causing COVID-19 has rapidly turned into a pandemic, infecting millions and causing 1 157 509 (as of 27 October 2020) deaths across the globe. In addition to studying the mode of transmission and evasion of host immune system, analysing the viral mutational landscape constitutes an area under active research. The latter is expected to impart knowledge on the emergence of different clades, subclades, viral protein functions and protein–protein and protein–RNA interactions during replication/transcription cycle of virus and response to host immune checkpoints. In this study, we have attempted to bring forth the viral genomic variants defining the major clade(s) as identified from samples collected from the state of Telangana, India. We further report a comprehensive draft of all genomic variations (including unique mutations) present in SARS-CoV-2 strain in the state of Telangana. Our results reveal the presence of two mutually exclusive subgroups defined by specific variants within the dominant clade present in the population. This work attempts to bridge the critical gap regarding the genomic landscape and associate mutations in SARS-CoV-2 from a highly infected southern region of India, which was lacking to date.